Effect of Heat Stress on the Antioxidant Activity of Boar Ejaculate Revealed by Spectroscopic and Electrochemical Methods - Horký, Pavel; Tmejová, Kateřina; Kenšová, Renáta; Cernei, Natalia Vladimirovna; Kudr, Jiří; Ruttkay-Nedecký, Branislav; Sapáková, Eva; Adam, Vojtěch; Kizek, René (ESG, 2015)
An effect of heat stress on antioxidant activity and overall quality of boar ejaculates was monitored. The samples of boar ejaculates were divided into two groups according to ejaculate quality. In the group A, regarding antioxidant activity a decreased value of N,N-dimethyl -1,4-diaminobenzene method by 71 %, an increase in 2,2-diphenyl-1-picrylhydrazyl method by 104 %, and decrease in superoxide dismutase activity by 39 % was determined. Results of the metal content were as follows decrease in levels of copper by 60 % and zinc by 52 %. Also decreases in metallothionein content by 64 %, and in pH by 11 % were recorded. In the group B, in antioxidant activity again a decreased value of DMPD by 68 %, and an increase in DPPH by 207 % was recorded. In addition reduced levels of copper by 78 %, zinc by 30 %, metallothionein by 64 %, and value of pH by 11 % were determined. The results show that heat stress induces an increase in protection against oxidative stress; in addition, levels of metallothionein, zinc and copper in the boar ejaculates in both groups are decreased when compared to day 0.

An effect of heat stress on antioxidant activity and overall quality of boar ejaculates was monitored. The samples of boar ejaculates were divided into two groups according to ejaculate quality. In the group A, regarding antioxidant activity a decreased value of N,N-dimethyl -1,4-diaminobenzene method by 71 %, an increase in 2,2-diphenyl-1-picrylhydrazyl method by 104 %, and decrease in superoxide dismutase activity by 39 % was determined. Results of the metal content were as follows decrease in levels of copper by 60 % and zinc by 52 %. Also decreases in metallothionein content by 64 %, and in pH by 11 % were recorded. In the group B, in antioxidant activity again a decreased value of DMPD by 68 %, and an increase in DPPH by 207 % was recorded. In addition reduced levels of copper by 78 %, zinc by 30 %, metallothionein by 64 %, and value of pH by 11 % were determined. The results show that heat stress induces an increase in protection against oxidative stress; in addition, levels of metallothionein, zinc and copper in the boar ejaculates in both groups are decreased when compared to day 0.
Effect of Heat Stress on the Antioxidant Activity of Boar Ejaculate Revealed by Spectroscopic and Electrochemical Methods
Keywords: Boar ejaculates; Heat stress; Antioxidant activity; Quality of ejaculates; Boar ejaculates; Heat stress; Antioxidant activity; Quality of ejaculates